Function Notation “f of x” Input = x Output = f(x) = y
(x, y) (x, f(x)) (input, output) y = – 3x+6 f(x) = – 3x+6 x y x f(x) Before… Now… y = – 3x+6 f(x) = – 3x+6 x y x f(x) -2 -1 1 2 12 -2 -1 1 2 12 (x, y) (x, f(x)) 9 9 6 6 3 3 (input, output)
g(2) = 2 3 g(5) = Find g(2) and g(5). Example Find g(2) and g(5). g = {(1, 4),(2,3),(3,2),(4,-8),(5,2)} g(2) = 2 3 g(5) =
Consider the function h= { (-4, 0), (9,1), (-3, -2), (6,6), (0, -2)} Example Consider the function h= { (-4, 0), (9,1), (-3, -2), (6,6), (0, -2)} Find h(9), h(6), and h(0).
Example. f(x) = 2x2 – 3 Find f(0), f(-3).
Example. f(x) = 3x2 +1 Find f(0), f(-1).
What are your questions?